Cutaneous sarcoidosis. A case report - Elizabet Fernández López; Adialys Acosta Rodríguez; Daymí Martínez Rodríguez; Caridad Socorro Castro (Medisur)
Sarcoidosis is a systemic granulomatous disease of unknown cause, with a higher prevalence in females, between 20 and 40 years of age; characterized by the formation of non-caseating granulomas in different organs. Exclusive skin involvement is rare, as it is described in only 4-5% of patients, since skin lesions may appear before or after systemic involvement, or coincide with it. The case of a 35-years-old patient with skin lesions of four years of evolution is presented. Considering the clinical case and histopathology, the diagnosis of chronic and asymptomatic cutaneous sarcoidosis was concluded. It is a very polymorphic disease in its skin manifestations, which makes it a great simulator, and its diagnosis constitutes a challenge for the dermatologist.